The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/10749357.2016.1251742
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water-based exercises on balance in persons post-stroke: a randomized controlled trial

Abstract: A combination of water- and land-based exercises has potential for improving balance. The results of this study extend the work showing benefit of water-based exercise in chronic and less-impaired stroke groups to patients with sub-acute stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 27 publications
0
45
0
2
Order By: Relevance
“…It has been shown that stroke is the most debilitating disease in the elderly, which greatly affects their quality of life. In this context, Pinedo et al (2017), Chan et al (2017), Katona et al (2015), Opara and Jaracz (2010), Jafari andDalvandi (2014), Fatahi et al (2008) also confirmed the poor quality of life of stroke patients in their findings (Opara and Jaracz, 2010;Pinedo et al, 2017;Chan et al, 2017;Katona et al, 2015;Jafari and Dalvandi, 2014;Attar Sayyah et al, 2016). But according to the results of this study, the quality of life and its indicators have improved somewhat in these patients by improving exercise and dynamic neuromuscular stability exercises.…”
Section: Discussionmentioning
confidence: 82%
“…It has been shown that stroke is the most debilitating disease in the elderly, which greatly affects their quality of life. In this context, Pinedo et al (2017), Chan et al (2017), Katona et al (2015), Opara and Jaracz (2010), Jafari andDalvandi (2014), Fatahi et al (2008) also confirmed the poor quality of life of stroke patients in their findings (Opara and Jaracz, 2010;Pinedo et al, 2017;Chan et al, 2017;Katona et al, 2015;Jafari and Dalvandi, 2014;Attar Sayyah et al, 2016). But according to the results of this study, the quality of life and its indicators have improved somewhat in these patients by improving exercise and dynamic neuromuscular stability exercises.…”
Section: Discussionmentioning
confidence: 82%
“…The average age of participants was 59.3 years and the majority of studies originated from Korea and Europe, and two from China. Participants were inpatients in five trials [31, 34, 38, 42, 48], outpatients in two trials [47, 49], both inpatients and outpatients in one trial [40], and community-dwelling in one trial [32]. Four trials did not report the source of subjects [30, 33, 39, 41].…”
Section: Resultsmentioning
confidence: 99%
“…The styles of hydrokinesitherapy employed were diverse. They included aquatic physical exercise [32, 33, 39, 47, 48], aquatic treadmill exercise [31, 34, 40, 41] and Halliwick [30, 38, 42, 49] performed in these trials. The frequency of hydrokinesitherapy were heterogeneous, with sessions ranging from 2 to 6 times per week, lasting between 30 and 60 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations